The `aggressive style`: genesis of an ambiguous resource for Swiss hockey and football players - Moret, O.; Traclet, A.; Clémence, A.; Ohl, F. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
In this study, we investigated what drives players to endorse an aggressive style in Swiss ice hockey and football. We selected a sample of 16 players on the basis of their penalty statistics. We used semi-directed retrospective interviews to collect players`; biographic narratives. The results show a socialization process into an aggressive style, supported by the dominant gender and socialization norms of the sport, which is under the influence of the structure of the sports organization. However, there are large differences between players, with only some of them adopting an aggressive style. Although many studies have underlined the influence of moral disengagement, the present results suggest that time also matters and that the diversity of career paths may explain the diversity in attitudes. Socialization differences in the sports field, bodily capital, a career path marked by thwarted reputation are the key factors that drive players to adopt an aggressive style.